Yeha, Äthiopien - Gerlach, Iris (e-Forschungsberichte des DAI, 2023)
The research in Yeha, 35 km to the northeast of Aksum, is devoted to a systematic examination of the cultural relations between South Arabia and East Africa. In 2012/13 the work of the Ethiopian-German project was concentrated on archaeological and conservational work on the monumental buildings of the site (early 1st millennium BC), on excavations in a cemetery and on archaeological examinations in the church forecourt and below a planned site museum.